PENERAPAN DATA MINING DALAM MEMPREDIKSI PEMBELIAN SEMEN - Rika Harman (Computer Based Information System Journal, 2019)
When faced with a decision to determine one choice it is sometimes a very difficult thing, this can occur due to lack of knowledge and supporting data that exists. Supporting data is usually not too difficult to find because it can be taken from our own environment or on our own, because without realizing it around us it is basically a very large and large collection of data but sometimes it is not utilized because it cannot use it. For example, this can be seen in the Batam Saddhana Legenda Building Shop, in principle, the building store is the same as the other building shops. But the problem arising from shop owners was when determining the purchase of cement as the main ingredient in building construction. If you prioritize closeness or good relations with sponsors and sponsors' contributions to the store, the shop owner will not be difficult to determine which supplier to contact, but because you have to learn the tendency of the buyer which brand they prefer, the problem will be complicated. Because the shop owner must order products that are tailored to consumer demand, if this is not done then what will happen to the existing customers will be disappointed because the product they want does not exist, even the shop owner must put stock for a long time that can harm the shop owner own. By applying the data mining classification technique to effective cement purchases at the Saddhana Shop, it is hoped that later it can produce a knowledge that can be used for decision making in effective cement purchases from suppliers.